Sirtuin1 mitigation of calcium oxalate nephropathy via enhancing itaconate abundance through reduction of histone trimethylation - Xiangyang Yao; Haoran Liu; Chen Duan; Yangjun Zhang; Xiaoliang Wu; Bo Li; Sheng Li; Yan Gong; Tongzu Liu; Xinghuan Wang; Hua Xu (Clinical and Translational Medicine)
Abstract Background Clinical therapeutic approaches to prevent and treat renal injury in patients with acute kidney injury (AKI) and chronic kidney disease (CKD) induced by calcium oxalate (CaOx) are limited. As a pivotal deacetylase, Sirtuin1 (Sirt1) exhibits notably anti‐inflammatory effects, but its metabolic mechanism in regulating CaOx nephropathy remains unexplored. Methods We analysed organic acid metabolism in kidney using the nontargeted metabolome and identified key targets by RNA‐seq. Evaluate renal injury and oxidative stress using techniques such as Positron Emission Tomography‐Computed Tomography (PET/CT) and transmission electron microscope. The protective mechanisms of Sirt1 against CaOx‐induced kidney injury and subsequent crystal deposition were demonstrated using in vitro coculture systems and in vivo Sirt1 conditional knockout mice. Results We found that Sirt1 has a significant protective effect on renal injury and oxidative stress induced by CaOx. Sirt1 expression decreases in CaOx nephropathy mice, and activation of Sirt1 reduces CaOx‐induced kidney injury and crystal deposition by increasing the level of itaconate. In addition, it was found that Sirt1 enhances immunoresponsive gene 1 and inhibits Sdha by trimethylating histones, thereby regulating the oxidation levels of itaconate and succinate. Furthermore, we emphasise the valuable role of Sirt1 agonists and exogenous itaconate in alleviating crystal induced kidney injury. Conclusions Our study revealed a previously unknown function of Sirt1 in CaOx nephropathy. By regulating itaconate level through epigenetic, Sirt1 protects against renal inflammation and oxidative damage induced by CaOx. Our preclinical data suggest that targeted Sirt1 agonism represents a promising therapeutic intervention for progressive crystallopathic nephropathy, potentially disrupting the inflammation–crystallisation vicious cycle. Highlights Sirt1 is significantly reduced in CaOx‐induced nephropathy models in vivo and calcium oxalate monohydrate (COM) induced in vitro. Sirt1 in macrophages alleviated CaOx‐induced kidney injury and crystal deposition via elevating itaconate levels. Conditional knockout of Sirt1 in vivo significantly exacerbates renal crystal deposition and function damage. We accurately evaluated CaOx‐induced renal inflammation status by micro 18F‐FDG PET/CT, and observed macrophage phagocytosis and encapsulation of crystals exposed to epithelial cells through scanning electron microscopy. Sirt1 agonists can be used as preventative and therapeutic agents for CaOx nephropathy, and exogenous supplementation of itaconate effectively alleviated renal crystallisation and inflammatory damage.